A-DROP: A predictive model for the formation of oil particle aggregates (OPAs). Issue 1 (15th May 2016) - Zhao, Lin; Boufadel, Michel C.; Geng, Xiaolong; Lee, Kenneth; King, Thomas; Robinson, Brian; Fitzpatrick, Faith
Abstract: Oil–particle interactions play a major role in removal of free oil from the water column. We present a new conceptual–numerical model, A-DROP, to predict oil amount trapped in oil–particle aggregates. A new conceptual formulation of oil–particle coagulation efficiency is introduced to account for the effects of oil stabilization by particles, particle hydrophobicity, and oil–particle size ratio on OPA formation. A-DROP was able to closely reproduce the oil trapping efficiency reported in experimental studies. The model was then used to simulate the OPA formation in a typical nearshore environment. Modeling results indicate that the increase of particle concentration in the swash zone would speed up the oil–particle interaction process; but the oil amount trapped in OPAs did not correspond to the increase of particle concentration. The developed A-DROP model could become an important tool in understanding the natural removal of oil and developing oil spill countermeasures by means of oil–particle aggregation. Highlights: A new conceptual–numerical model, A-DROP, to predict OPA formation was developed. A new conceptual formulation of oil–particle coagulation efficiency was introduced. The model closely reproduced the oil trapping efficiency of experimental data. OPA formation in breaker, surf, and swash zone of nearshore environment was predicted.